2016
DOI: 10.1136/gutjnl-2016-312388.158
|View full text |Cite
|
Sign up to set email alerts
|

PTU-073 In Patients with IBD Switching from Originator Infliximab (Remicade) to Biosimilar Infliximab (CT-P13) Is Safe and Effective

Abstract: IntroductionBiosimilar infliximab (CT-P13) has been licensed for the treatment of IBD in Europe for over a year with the potential for significant cost savings. However, uptake in the UK has been slow primarily due to concerns over the lack of safety and efficacy data particularly with regard to switching patients from the originator product. We present the preliminary data from a controlled switch programme in a cohort of adult IBD patients.MethodsA prospective study was undertaken to assess the safety and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…All of the 27 observational, non-medical switching studies reported data on main efficacy parameters after switching compared with baseline/before switching (Table 2) [4352, 54, 58, 62, 63, 6568, 71, 72, 77, 79, 83, 8790, 105]. The originator biologics/biosimilars assessed were infliximab (20 studies [4352, 54, 58, 62, 63, 6568, 71, 72]), ESAs (two studies [77, 79]), insulin (two studies [83, 87]) and growth hormone (three studies [8890]).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All of the 27 observational, non-medical switching studies reported data on main efficacy parameters after switching compared with baseline/before switching (Table 2) [4352, 54, 58, 62, 63, 6568, 71, 72, 77, 79, 83, 8790, 105]. The originator biologics/biosimilars assessed were infliximab (20 studies [4352, 54, 58, 62, 63, 6568, 71, 72]), ESAs (two studies [77, 79]), insulin (two studies [83, 87]) and growth hormone (three studies [8890]).…”
Section: Resultsmentioning
confidence: 99%
“…The originator biologics/biosimilars assessed were infliximab (20 studies [4352, 54, 58, 62, 63, 6568, 71, 72]), ESAs (two studies [77, 79]), insulin (two studies [83, 87]) and growth hormone (three studies [8890]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations